Expression patterns of ethylene biosynthesis genes from bananas during fruit ripening and in relationship with finger drop - Hubert, Olivier (Oxford University Press, 2012)
BACKGROUND AND AIMS: Banana finger drop is defined as dislodgement of individual fruits from the hand at the pedicel rupture area. For some banana varieties, this is a major feature of the ripening process, in addition to ethylene production and sugar metabolism. The few studies devoted to assessing the physiological and molecular basis of this process revealed (i) the similarity between this process and softening, (ii) the early onset of related molecular events, between the first and fourth day after ripening induction, and (iii) the putative involvement of ethylene as a regulatory factor. This study was conducted with the aim of identifying, through a candidate gene approach, a quality-related marker that could be used as a tool in breeding programmes. Here we examined the relationship between ripening ethylene biosynthesis (EB) and finger drop in order to gain further insight into the upstream regulatory steps of the banana finger drop process and to identify putative related candidate genes. METHODS: Postharvest ripening of green banana fruit was induced by acetylene treatment and fruit taken at 1–4 days after ripening induction, and total RNA extracted from the median area [control zone (CZ)] and the pedicel rupture area [drop zone (DZ)] of peel tissue. Then the expression patterns of EB genes (MaACO1, MaACO2, MaACS1, MaACS2, MaACS3 and MaACS4) were comparatively examined in CZ and DZ via real-time quantitative polymerase chain reaction. PRINCIPAL RESULTS: Differential expression of EB gene was observed in CZ and DZ during the postharvest period examined in this study. MaACO1, MaACS2 and MaACS1 were more highly induced in DZ than in the control, while a slight induction of the MaACS4 gene was observed. No marked differences between the two zones were observed for the MaACO2 gene. CONCLUSIONS: The finger drop process enhanced EB gene expression including developmental- and ripening-induced genes (MaACO1), specific ripening-induced genes (MaACS1) and wound-induced genes (MaACS2). Thus, this process might be associated with a specific ethylene production in DZ of the pedicel area and the result of crosstalk between developmental, ripening and wound regulatory pathways. MaACO1, MaACS1, MaACS2, and to a lesser extent MaACS4 genes, which are more highly induced in DZ than in CZ, could be considered as putative candidates of the finger drop process.